2016
DOI: 10.18632/oncotarget.9239
|View full text |Cite
|
Sign up to set email alerts
|

AJUBA promotes the migration and invasion of esophageal squamous cell carcinoma cells through upregulation of MMP10 and MMP13 expression

Abstract: The LIM-domain protein AJUBA has been reported to be involved in cell-cell adhesion, proliferation, migration and cell fate decision by acting as a scaffold or adaptor protein. We previously identified AJUBA as a putative cancer gene in esophageal squamous cell carcinoma (ESCC). However, the function and underlying mechanisms of AJUBA in ESCC remain largely unknown. In the present study, we detected AJUBA levels in ESCC tumor tissues and in corresponding adjacent non-tumor tissues by immunohistochemistry (IHC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 38 publications
(42 reference statements)
5
48
1
3
Order By: Relevance
“…LIMD1 functions as a tumor suppressor and is frequently inactivated in lung cancer. In contrast, Shi et al reported AJUBA promotes migration and invasion of esophageal squamous cell carcinoma cells through upregulating MMP10 and MMP13 . Furthermore, influence of AJUBA proteins on EMT is also complicated and dynamic.…”
Section: Discussionmentioning
confidence: 94%
“…LIMD1 functions as a tumor suppressor and is frequently inactivated in lung cancer. In contrast, Shi et al reported AJUBA promotes migration and invasion of esophageal squamous cell carcinoma cells through upregulating MMP10 and MMP13 . Furthermore, influence of AJUBA proteins on EMT is also complicated and dynamic.…”
Section: Discussionmentioning
confidence: 94%
“…More recently, another study showed that the AJUBA level was significantly higher in ESCC tissues compared with matched adjacent tissues. AJUBA functions as an oncogenic gene in both in vitro and in vivo experiments 42 .…”
Section: Discussionmentioning
confidence: 99%
“…We further validated those genes identified by mass spectrum that have also been reported to be involved in metastasis and invasion (15)(16)(17)(18) by quantitative RT-PCR and Western blotting assays. mRNA levels of Wnt7a, MMP1, MMP10, and S100A8 significantly increased in 5637 HMI compared with 5637 NMI cells ( Fig.…”
Section: Identification Of Dysregulated Proteins In 5637 Hmi Cells Comentioning
confidence: 92%